2022
DOI: 10.1186/s13046-021-02175-3
|View full text |Cite
|
Sign up to set email alerts
|

Circ_0000658 knockdown inhibits epithelial-mesenchymal transition in bladder cancer via miR-498-induced HMGA2 downregulation

Abstract: Background Epithelial-mesenchymal transition (EMT) has been associated with the angiogenesis and oncogenic phenotypes of multiple malignant tumors including bladder cancer (BCa). Circular RNAs (circRNAs) are recognized as crucial regulators in the EMT. This study aims to illustrate the possible role of circular RNA_0000658 (circ_0000658) in BCa and the underlying molecular mechanism. Methods The expression of circ_0000658, microRNA (miR)-498, and h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…24 Circ_0000658 acted as a tumour-promoting factor in bladder cancer via regulating the miR-498/HMGA2 axis. 25 Circ CUL2 served as an antitumor factor to facilitate PPP6C expression and colorectal cancer progression via absorbing miR-208a-3p. 26 Moreover, the roles of circRNAs in the HCC process have been revealed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…24 Circ_0000658 acted as a tumour-promoting factor in bladder cancer via regulating the miR-498/HMGA2 axis. 25 Circ CUL2 served as an antitumor factor to facilitate PPP6C expression and colorectal cancer progression via absorbing miR-208a-3p. 26 Moreover, the roles of circRNAs in the HCC process have been revealed.…”
Section: Discussionmentioning
confidence: 99%
“…With the development and application of RNA sequencing technology, a variety of abnormally expressed circRNAs have been discovered, and further study has found that they play an important role in cancer progression 24 . Circ_0000658 acted as a tumour‐promoting factor in bladder cancer via regulating the miR‐498/HMGA2 axis 25 . Circ CUL2 served as an antitumor factor to facilitate PPP6C expression and colorectal cancer progression via absorbing miR‐208a‐3p 26 .…”
Section: Discussionmentioning
confidence: 99%
“…reported that circST6GALNAC6, modulated by the transcription factor SP1, inhibits BCa metastasis through binding miR-200a-3p to regulate the STMN1/EMT axis ( 48 ), and Su et al. revealed that Circ_0000658 enhanced BCa cell proliferative, migratory and invasive capacities by miR-498/HMGA2/EMT signaling axis ( 49 ). As reported, circCEP128 promotes BCa progression through activating MAKP signaling pathway via miR-145-5p/MYD88 path ( 50 ).…”
Section: Discussionmentioning
confidence: 99%
“…The interaction between miR-532-3p and TXNIP protein was determined using an RIP kit (Millipore, Billerica, MA) [ 22 ]. Lysed cells were centrifuged to collect the supernatant.…”
Section: Methodsmentioning
confidence: 99%